Impulsivity and compulsivity in compulsive buying - Eliyahu, Sapir; Rahamim, Shir; Natan, Noy; Weinstein, Aviv M. (Frontiers in Psychiatry, 2025)
IntroductionThe current study examined impulsivity and compulsivity in individuals with compulsive buying (CB) and those without CB.MethodsThe sample consisted of 120 participants (97 women, 23 men), undergraduate psychology students (age: M = 24.5, SD = 3.9). Participants were divided into two groups: individuals who scored high on a compulsive buying scale (CBS) and individuals who scored low on the CBS. Questionnaires measured impulsivity (Barratt Impulsiveness Scale) and compulsivity (Yale-Brown Obsessive-Compulsive Scale), along with the computerized experiential delay discounting task (EDT), response inhibition (Go/No-Go), and selective attention (Dot-Probe). ResultsThe questionnaires indicated higher levels of impulsivity and compulsivity in the experimental group. Secondly, compulsive buyers exhibited higher error rates in the No-Go commission condition during the second part of the Go/No-Go task, indicating an impairment in response inhibition. No differences were found in delay discounting or selective attention measured by the Dot-Probe task. Additionally, compulsive buying scores positively correlated with state anxiety scores. In a following experiment, 40 students were divided into two groups: individuals with high CBS scores and individuals with low CBS scores. They performed a simulated shopping experiment using the ASOS shopping website, with their responses recorded on Zoom. Compulsive buyers were quicker to add items to the shopping cart and spent more money than non-compulsive buyers. Compulsive buying scores were also associated with impulsivity and sensation-seeking scores. Impulsivity, but not sensation-seeking, contributed to the variance of compulsive buying scores. DiscussionThis study showed impaired inhibition with a higher cognitive load on the Go/No-Go task in compulsive buyers. Secondly, there was evidence for impulsivity indicated by negative correlations between compulsive buying scores and reaction times on the in the No-Go commission condition on the Go/No-Go task and on the Dot-Probe task. Finally, in a simulation of real-life shopping, compulsive buyers were faster to choose items, and they paid more for them. This evidence suggests that the effects of compulsive buying on cognitive function are often subtle and a real-life simulation that uniquely demonstrates this impairment.